Self-Efficacy's Impact on Academic Achievement During the Pandemic: Dampak Efikasi Diri terhadap Prestasi Akademik Selama Pandemi - Nurul Syifa, Oktaviani (Journal of Islamic and Muhammadiyah Studies, 2024)
The study aimed to explore the relationship between self-efficacy and academic achievement during the pandemic among students at Muhammadiyah University of Sidoarjo. Self-efficacy, representing belief in one's ability to manage tasks, and academic achievement, denoting knowledge mastery, were assessed. Utilizing a correlational quantitative approach, data from 345 students were collected through Likert scale-based psychology assessments. Analysis via Pearson Product Moment correlation revealed a significant positive relationship (r = 0.431, p < 0.05) between self-efficacy and academic achievement. The findings imply that higher self-efficacy corresponds to increased academic performance, emphasizing the importance of self-belief in educational outcomes. Highlight: Relationship assessment: Investigated the connection between self-efficacy and academic achievement. Methodological approach: Employed correlational quantitative methodology for data analysis. Significance: Identified a positive correlation between self-efficacy and academic performance. Keywoard: Self-efficacy, Academic achievement, Pandemic, Correlational study, Muhammadiyah University.